ANALISIS REAKSI PASAR TERHADAP PENGUMUMAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2013 - NURMA YUNITA; MICHAEL HADJAAT; MARYAM NADIR (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
This study aims to determine the result of market reaction to dividend announcement and examine the differences in differences in market reaction before and after the dividend announcement on manufacturing companies in the stock exchange indonesia. As for the variables used in this study is the abnormal return and trading volume activity with the event study method. In the calculation of abnormal return and trading volume activity were then tested by testing paired samples t-test. The number of samples in this study were 36 compnies manufacturing for the period 2011-2013. The analysis results on the testing of the abnormal return on the announcement of the dividend showed a significant difference before and after the dividend announcement. It can be proved from the results of paired samples t-tes with a probability below 0.05 are on day -1,+1 and -2,+2 with a value of 0.023 0.05 and 0.039 0.05. while testing trading volume activity (TVA) to the announcement of the dividend showed no significant difference from the result of paired samples t-tes with a probability of 0.05 is at the -1,+1, -2,+2 and -3,+3 with a value of 0.315 0.05, 0.181 0.05 and 0.315 0.05. so conclusions significant difference in abnormal return before and after the date of the dividend announcement and the absence of significant difference in the trading volume activity before and after the announcement date.Keyword: Dividend Announcement, Abnormal Return, Trading Volume Activity